The Speaking Body and the Silent Mouth: Communication Techniques and Tactics in Criminal Activities and Occupations - Bodner, John (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2019)
This paper analyzes two micro-case studies to expand our understanding of communication techniques in criminal practices. In the first instance the torture of a suspected drug thief by two street kid research participants is investigated as both an instrumental trial by ordeal and a communication strategy in a media poor community. In the second case study, excerpts from occupational folklore and lifestory interviews are presented to demonstrate the complex ways in which silence is used and resisted in the stories of illegal marijuana growers in a small village in British Columbia.